Influence of microstructure on hardness and thermal conductivity of hardmetals. (April 2020) - Vornberger, A.; Pötschke, J.; Gestrich, T.; Herrmann, M.; Michaelis, A.
Abstract: Hardmetals or cemented carbides are used in a wide range of applications due to their excellent mechanical properties. WC-Co hardmetals with the same room temperature hardness can be obtained by different combinations of the WC grain size and cobalt content. However, the thermal conductivity of such hardmetal grades is not equal. Applications such as cutting may require a certain combination of hardness and thermal conductivity, which means that a targeted adjustment is desirable. In this study a wide range of hardmetal grades was studied in respect of microstructure, hardness and thermal conductivity in the temperature range between 20 °C and 1000 °C. Results show that thermal conductivity is considerably influenced by Co content, WC grain size and Cr3 C2 content. Furthermore, hardmetal grades with the same hardness at room temperature retain hardness very differently at elevated temperatures. For the selection of hardmetal grades for high temperature applications these findings help to choose the right composition in regard to Co content and WC grain size. Highlights: Hardness and thermal conductivity of hardmetals was studied between 20 °C to 1000 °C Correlation between these properties and microstructure is discussed Hot hardness changes at 600 °C drastically Thermal conductivity decreases for coarse hardmetal grades but not for fine grades